2017
DOI: 10.1007/s00223-017-0371-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Quantitative Evaluation of Muscle and Bone Wasting Induced by Botulinum Toxin in Mice Using Microcomputed Tomography

Abstract: Muscle and bone masses are highly correlated and muscles impose large loads on bone. Muscle wasting that accompanies bone loss has been poorly investigated. 21 female mice were spread into seven groups. At day 0, 18 mice received Botulinum toxin (BTX) injection in the quadriceps muscle to induce paralysis of the right hind limb; the left contralateral side was used as control. Mice were sacrificed at 7, 14, 21, 28, 56 and 90 days post-injection. A remaining group was sacrificed at day 0. Trabecular bone volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…There are few articles in the literature on the natural history of condylar bone changes in patients with TMJD. Significant condylar bone changes are found in 68% of cases at the TMJ after radiological follow-up during 13.4 months [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] in patients presenting TMJD 46 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There are few articles in the literature on the natural history of condylar bone changes in patients with TMJD. Significant condylar bone changes are found in 68% of cases at the TMJ after radiological follow-up during 13.4 months [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] in patients presenting TMJD 46 .…”
Section: Discussionmentioning
confidence: 98%
“…It leads to a transient muscle paralysis by a "functional denervation" 2 . In laboratory animals, a single BTX injection in the quadriceps induces a disuse bone loss at the tibia and femur with a considerable muscle wasting 3,4 . In humans, the effect of BTX disappears after two to four months and muscle strength starts to reappear three to four months later 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Also, repetitive interventions demonstrated bone loss in the mandibular angle in a clinical trial . The lower limbs of female mice also experienced bone loss, but the long‐term evaluation showed muscle recovery at 56 days whereas femur deterioration was reversed after 90 days . However, the recovery might be comparatively slower in the masticatory apparatus, as demonstrated by a study in adult female rabbits, where the muscle still exhibited signs of atrophy and the condyle still showed a reduced bone quality 12 weeks after injecting BoNTA in the masseter muscle …”
Section: Discussionmentioning
confidence: 99%
“…43 The lower limbs of female mice also experienced bone loss, 46,47 but the long-term evaluation showed muscle recovery at 56 days whereas femur deterioration was reversed after 90 days. 47 However, the recovery might be comparatively slower in the masticatory apparatus, as demonstrated by a study in adult female rabbits, where the muscle still exhibited signs of atrophy and the condyle still showed a reduced bone quality 12 weeks after injecting BoNTA in the masseter muscle. 19 The mandibular condyle and the alveolar process are influenced differently by masticatory loading due to particular structural and anatomical features.…”
Section: Discussionmentioning
confidence: 99%
“…In the rat, we recently confirmed the vanishing effect of BTX and its effects both on muscle and on long bones. 4 Fourth, the authors indicate that there are only a few clinical studies on the effects of BTX treatment on bone. A recent study from our group identified alveolar and condylar bone changes in adult patients at the mandible after BTX injections into masticatory muscles.…”
mentioning
confidence: 99%